The use of virtual reality as an advertising tool for brand experience in Peru - Espinoza-Nieves, Javier (2022)
Recently, the advertising industry has implemented new methods to improve the relationship between brands and their consumers. To understand how to achieve this effect in a positive way, several studies have turned to the examination of advertising actions aimed at boosting brand experience. However, there are few studies that deepen the knowledge of the importance of creating brand experiences through innovative communication technologies such as virtual reality (VR). The present research explores how the use of VR in advertising helps in the generation of brand experiences. A qualitative methodology of phenomenological design was used with advertising professionals in the city of Lima. In addition, the exploratory scope of the analysis followed a descriptive coding process. It was evidenced that the properties of VR, such as immersion, presence, and its sensory capabilities are crucial to promote brand experiences with greater intensity. This category of virtual brand experiences influences brand image, affects purchase intentions and, above all, builds brand loyalty.